Interacciones medicamentosas en prescripciones médicas del servicio de ginecología del Hospital Regional Docente de Trujillo en el período de octubre 2006 - febrero 2007 - Chávez Garrido, Gina Lucy (2007)
The present works is a descriptive, retrospective and traverse study. This study one carried out in a total of 1196 prescriptions, which fulfilled an inclusion approach and exclusion, in the period of October 2006-February 2007, which were subjected to the evaluation to determine the drug interaction that were presented in the prescriptions, by means of the bibliographical method – analytic. The objectives were to identify and quantify the most common drug interactions in the Gynecology Service, as well as identifying drug interactions greater clinical significance and finally describe the types of drug interactions found in medical prescriptions. The most common drug interactions were: Nifedipine-Magnesium Sulfate (37,31%); Gentamicin-Ketorolac (13,43%) y Ceftriaxone-Amikacin (8,96%), the greater clinical significance accounted for 9% of the total interactions, and interaction Gentamicina-Furosemida the most significant drug interactions and finally the kind of pharmacodynamic were the most numerous accounting for 62,69%; while the pharmacokinetic accounted for 31,34% and unknown the 5,97%.